Wednesday

October 22, 2014

October 22, 2014

Posted by **Jon** on Saturday, March 1, 2008 at 7:46pm.

(x-p)(x-q)=0

(x--3/4)(x-4)=0

(x+3/4)(x-4)=0

x^2-3x+3=0(answer)

- Algebra II -
**mk-tintin**, Saturday, March 1, 2008 at 7:53pm(x+3/4)(x-4)=x²+3/4x-4x-3=x²-(13/4)x-3

if u want to know if your answer is right or false, it's easy

f(x)=x²-(13/4)x-3

and u can verify if f(4)=0 and f(-3/4)=0

- Algebra II -
**Reiny**, Saturday, March 1, 2008 at 9:31pmif the roots are -3/4 and 4 then the factors that will form your equation are

(4x+3) and (x-4)

so (4x+3)(x-4) = 0 or

4x^2 13x - 12 = 0

**Answer this Question**

**Related Questions**

algebra - 1)Solve by factoring:5x^2=4-19x answer=-4,1/5 2)Which quadratic ...

algebra - Write the quadratic equation in factored form. Be sure to write the ...

Math(Algebra) - An arrow is shot vertically upward from the top of a cliff 80 ...

Algebra - 1)Find the exact solutions to 3x^2=5x-1 using the quadratic formula. ...

maths - find the roots of the equation X(square)+7x equal to 0.(b)write down the...

Maths - The sum of the squares of three consecutive positive integers is 365 ...

Math (Algebra) - If the ratio of the roots of the quadratic equation x^2−...

Algebra2 - Find the polynomials roots to each of the following problems: #1) x^2...

Math - 1)Write a quadratic equation with integer coefficients that has -4+7i(...

Algebra - Write a quadratic equation in the variable X. Write in standard form: ...